Effects of large‐scale climate anomalies on crop reference evapotranspiration in the main grain‐production area of China. (30th October 2018) - Liu, Bingjun; Huang, Zeqin; Chen, Xiuhong; Wang, Zhaoli
Abstract : Crop reference evapotranspiration (ET0 ), which connects the energy and water balance, is an important indicator used in water resource management and agricultural production. On the basis of daily meteorological data from 479 observation stations, we investigate changes in ET0 and associated climate factors across the main grain‐producing area (MGPA) of China from 1960 to 2015. The Mann–Kendall test and Sen's slope estimator were applied to detect trends in ET0, and regression analyses and composite analyses were used to evaluate the contributions of climatic variables and large‐scale anomalies that may affect ET0 . The results of this study show that ET0 in the MGPA decreased (−2.67 mm/decade) during summer throughout the past 56 years, and that this change is largely attributable to decreased sunshine duration and wind speed (WS). Furthermore, decreased WSs in the 850‐hpa geostrophic wind field, are responsible for decreases in ET0 in Northeast China Region (−1.85 mm/decade), which affect ET0 by significantly weakening the observed surface WS. Meanwhile, significant low cloud cover variations accounted for the decrease in ET0 in the Huang‐Huai‐Hai Region (−7.85 mm/decade), Loess Plateau Region (−2.91 mm/decade), Yangtze River Region (−3.96 mm/decade), and Southwest China Region (−2.71 mm/decade). However, decreases in the integrated atmospheric water vapour content (IWVC), which act to weaken the surface relative humidity, are hypothesised to increase ET0 in the South China Region (1.25 mm/decade). Abstract : Topographic map of China with 479 meteorological stations across main grain‐producing area (MGPA).